L’inquiétante sincérité : Baudelaire et Chopin lus par André Gide - Voegele, Augustin (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
Why does André Gide so often compare Chopin to Baudelaire? For several reasons: because for him, the two artists are unique, irreplaceable, incomparable; because both were initially misunderstood; and because they are both classics of the nineteenth century. In other words, what distinguishes them, according to Gide, is their aesthetics of discretion, which is very similar to the one he develops in his own works – particularly those in which he defends the homosexual cause.